2020
DOI: 10.1038/s41467-020-15892-8
|View full text |Cite
|
Sign up to set email alerts
|

Chemical modifications of adenine base editor mRNA and guide RNA expand its application scope

Abstract: CRISPR-Cas9-associated base editing is a promising tool to correct pathogenic single nucleotide mutations in research or therapeutic settings. Efficient base editing requires cellular exposure to levels of base editors that can be difficult to attain in hard-to-transfect cells or in vivo. Here we engineer a chemically modified mRNA-encoded adenine base editor that mediates robust editing at various cellular genomic sites together with moderately modified guide RNA, and show its therapeutic potential in correct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 36 publications
(61 reference statements)
2
65
1
Order By: Relevance
“…Without a double-strand DNA break, base editing can lead to single nucleotide conversion and therefore can be used as a reliable tool for genome editing and potentially correct the disease-related mutations in the genome ( 16 ). In vivo mRNA delivery of base editors using lipid nanoparticles (LNPs) has attracted great interest ( 19 , 20 ), whereas most of the current studies used viral vectors for in vivo base editing or direct gene engineering on zygotes ( 16 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Without a double-strand DNA break, base editing can lead to single nucleotide conversion and therefore can be used as a reliable tool for genome editing and potentially correct the disease-related mutations in the genome ( 16 ). In vivo mRNA delivery of base editors using lipid nanoparticles (LNPs) has attracted great interest ( 19 , 20 ), whereas most of the current studies used viral vectors for in vivo base editing or direct gene engineering on zygotes ( 16 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Base editors delivered as chemically modified mRNA were tested in vitro to correct the most common CFTR nonsense mutation, W1282X. This study obtained efficient reversion of this point mutation and suggests a new method to deliver base editors [79].…”
Section: Correction Of Point Mutation With Base Editorsmentioning
confidence: 99%
“…Moreover, due to increased interest in BE, non-viral vectors are under investigation to replace viral constructs as delivery systems [ 21 ]. Jiang et al demonstrated a successful delivery of ABE using lipid nanoparticles in Tyrosinemia I mice, correcting the gene mutation and showing the promise of the BE approach [ 128 ]. Despite the far-reaching capabilities of the BE strategy, a major limitation of this technique has been the ability to generate precise edits beyond the allowed transition mutations.…”
Section: Targets and How To Reach Them: Dna And Rnamentioning
confidence: 99%